How Does ROGIC Affect Financial Performance through Intellectual Capital of Modern Sharia Banking registered with the OJK? - Triyanto, Fiqi; Nadifah, Asprilya; Parlina, Nurhana Dhea (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study examines the effect of the Intellectual Capital Growth Rate (ROGIC) on the financial performance of Islamic banks in Indonesia, with Intellectual Capital (IC) as a mediating variable. Design/Methodology/Approach: Using a quantitative approach and path analysis, data from seven Islamic banks registered with the OJK for the 2018–2023 period were analyzed to measure the direct and indirect effects of ROGIC on Return on Assets (ROA). Findings: The results showed that ROGIC did not significantly affect ICs in most banks, and its immediate impact was limited. However, in banks such as KB Bukopin Syariah and BTPN Syariah, ROGIC has a significant indirect effect on financial performance through IC. These findings emphasize the importance of effective IC management in improving financial performance. Research limitations/implications: The limitations of the study include a limited sample, so further research with a larger sample and additional variables is recommended. Practical implications: The practical implication is the need for IC optimization by Islamic bank management. This research contributes to the understanding of the relationship between intellectual capital growth and financial performance in the context of Islamic banking. Paper type: Research paper